Alokasi Dana Desa (ADD) dan Kemandirian Sosial-Ekonomi Masyarakat Desa: Kasus di Desa Senduro, Kabupaten Lumajang - Sholahudin, Umar; Sair, Abdus (Universitas Negeri Malang, 2022)
Artikel ini akan mengulas tentang pelaksanaan Alokasi Dana Desa (ADD) dan dampaknya terhadap Kemandirian Sosial-Ekonomi Masyarakat Desa Senduro. Sejauh ini, penelitian tentang desa masih seputar soal kondisi desa dan masyarakat desa beserta problem-problemnya. Sementara yang berkaitan dengan pelaksanaan ADD dan dampaknya belum banyak mendapatkan perhatian. Padahal, kebijakan ADD diyakni dapat berkontribusi pada perbaikan dan peningkatan kemandirian desa, khususnya di bidang sosial-ekonomi masyarakat desa. Artikel ini adalah hasil penelitian dengan metode kualitatif dan pendekatan deskriptif. Hasil penelitiaan ini menunjukkan, bahwa pelaksanaan kebijakan ADD di Desa Senduro dijalankan sesuai kebutuhan masyarakat desa. Ada dua kebutuhan yang teridentivikasi, yakni pembentukan Senduro sebagai Desa Adat dan Pengembangan Desa Wisata. Pelaksanaan dua kebutuhan desa ini secara nyata memberikan dampak terhadap kemandirian sosial ekonomi desa. Program dan kegiatan dalam rangka pembentukan Desa Adat dan Pengembangan Desa Wisata dilakukan dengan semangat kebersamaan dan gotong royong. Ikatan sosial yang kuat diantara warga mampu membangun kemandirian ekonomi masyarakat. Pelaksanaan ADD secara gotong royong mampu membangun kemandirian sosial-ekonomi masyarakat Desa Senduro menjadi lebih produktif. Allocation of Village Funds and Socio-Economic Autonomy Of Village Communities: A Case in Senduro Village,Lumajang RegencyThis study aims to examine how the implementation of ADD and its impact on the Socio-Economic Independence of the Senduro Village Community, Senduro District, Lumajang Regency. This research is motivated by two important aspects that are currently happening and being experienced by the village. First, the condition of the village and village community, each of which struggles with socio-economic problems such as poverty, unemployment, and the village's economic level which is still weak and difficult to develop. Second, there is a very strategic and important opportunity for the improvement and improvement of the welfare of rural communities, namely through Law no. 6 of 2014 concerning Villages and Government Regulation No. 43 of 2014 concerning Implementing Regulations of Law Number 6 of 2014 concerning Villages. With the new legal basis, the village now has autonomy, both in governance and village financial management. The village fund allocation policy (ADD) is believed to be able to contribute to the improvement and improvement of village independence, especially in the socio-economic field of rural communities. This study uses a descriptive-qualitative approach. Descriptive research is research conducted with the main objective to describe the facts that occur objectively. This research is based more on collecting qualitative data in the form of informants' experiences which are presented in verbal form, especially those related to the implementation of ADD and its impact on the Socio-Economic Independence of the people of Senduro Village, Senduro District, Lumajang Regency. The research data obtained were analyzed using the theory of empowerment. The results of this study indicate that the implementation of ADD policies in Senduro Village is carried out according to the needs of the village community. There are two needs of villages that utilize ADD, namely the establishment of Senduro as a Traditional Village and Development of a Tourism Village. The implementation of these two village needs has a real impact on the socio-economic independence of the village. Community Programs and Activities of Senduro Village for the establishment of Senduro as a Traditional Village and Tourism Village Development is carried out in the spirit of togetherness and mutual cooperation. Strong social ties among citizens are able to build community economic independence. The implementation of ADD in mutual cooperation is able to build the socio-economic independence of the people of Senduro Village to be more productive.